Molecular and clinical characterization of Galectin‐9 in glioma through 1, 027 samples. Issue 5 (14th October 2019) - Yuan, Feng; Ming, Haolang; Wang, Yingshuai; Yang, Yihan; Yi, Li; Li, Tao; Ma, Haiwen; Tong, Luqing; Zhang, Liang; Liu, Peidong; Li, Jiabo; Lin, Yu; et al.
Abstract: In recent years, research on glioma immunotherapy have grown rapidly. However, the autoimmune‐like side effects that are caused by blocking immunological checkpoints hinder their clinical application in gliomas currently. Galectin‐9, a ligand for T‐cell immunoglobulin mucin 3, has shed a new light on the treatment of malignant glioma. However, the potential mechanism of Galectin‐9 is still under discussion. In this study, first, we methodically gathered 1, 027 glioma patients with RNA‐seq and 986 patients with survival data to explore the role and mechanism of Galectin‐9 in gliomas. Second, we analyzed glioma samples from 50 patients in the Department of Neurosurgery, Tianjin Medical University General Hospital. Finally, we found that Galectin‐9 was strongly upregulated in glioblastoma multiforme compared with normal brain tissues and lower‐grade glioma. Patients with Galectin‐9 overexpression had a significantly shorter overall survival. Moreover, the tissue microarray data displayed that the expression of Galectin‐9 in the core of tumor is higher than that in the border and was correlated with the shorter survival in glioma patients. Galectin‐9 is more highly expressed in the mesenchymal subtype of glioblastoma multiforme than in the other subtypes. Simultaneously, Galectin‐9 was closely associated with the immune response and lymphocyte activation, especially T‐cell activation. To further determine the underlying role of Galectin‐9 in the immune response, we selected seven immune metagenes. Through cluster analysis and correlation analysis, we discovered that Galectin‐9 was highly correlated with immune checkpoint molecules and M2 tumor‐associated macrophages. In summary, Galectin‐9 serves as a potential therapeutic target to treat glioblastoma multiforme. Abstract : In this study, we evaluated the expression status of Galecin‐9 and its associated biological processes and prognosis by analyzing RNA‐seq and clinical data from TCGA and CGGA databases, with the hope of obtaining a comprehensive understanding of Galectin‐9 and new findings in its use for the treatment of glioblastoma multiforme (GBM)